Risk management system in the natural gas distribution of Lima and Callao according guidelines “Recommendations on transmission and distribution practice” and risk management of the PMI Project (2008) - Luján Ruiz, Roger Orlando (2014)
The purpose of this research study is to analyze quantitative operational risk according to the guidelines of the practice recommendation “Recommendations on Transmission and Distribution Practice” , published by The Institution of Gas Engineers of Great Britain and the PMBOK . Chapter 11 , Managing Project Risk . This study was conducted in the Trunk pipeline system operated by Cálidda the Peru - Natural Gas from the City Gate located in Lurín , to Callao Terminal Station . The purpose of this study was to determine the levels of individual risk and safety of the general public due to the operation of the pipeline that operates Cálidda Trunk . In cases where the individual or social risks are considered intolerable compared to international standards mitigation measures associated with the operation to levels that can be considered consistent with best industry practices recommended risk.